2009
DOI: 10.1128/jvi.00011-09
|View full text |Cite
|
Sign up to set email alerts
|

DDX3 DEAD-Box RNA Helicase Inhibits Hepatitis B Virus Reverse Transcription by Incorporation into Nucleocapsids

Abstract: Viruses utilize host factors in many steps of their life cycles. Yet, little is known about host factors that contribute to the life cycle of hepatitis B virus (HBV), which replicates its genome by reverse transcription. To identify host factors that contribute to viral reverse transcription, we sought to identify cellular proteins that interact with HBV polymerase (Pol) by using affinity purification coupled with mass spectrometry. One of the HBV Pol-interacting host factors identified was DDX3 DEAD-box RNA h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
114
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(123 citation statements)
references
References 38 publications
6
114
1
Order By: Relevance
“…These results demonstrate that DDX19A specifically functions in HP-PRRSV RNA-induced IL-1b secretion by acting as the direct sensor, and other stimulators (such as polyI:C or ATP/LPS), respectively, activate NLRP3 inflammasome through different pathways. Recently, the DEAD/H-box helicase family members have been drawing more and more attention not only for their powerful capacities in detecting invading PAMPs as direct sensors (6, 36), but also for their key roles involved in viral replication (36,38,39,71). It has been demonstrated that DDX3 binds the HCV core FIGURE 8.…”
Section: Discussionmentioning
confidence: 99%
“…These results demonstrate that DDX19A specifically functions in HP-PRRSV RNA-induced IL-1b secretion by acting as the direct sensor, and other stimulators (such as polyI:C or ATP/LPS), respectively, activate NLRP3 inflammasome through different pathways. Recently, the DEAD/H-box helicase family members have been drawing more and more attention not only for their powerful capacities in detecting invading PAMPs as direct sensors (6, 36), but also for their key roles involved in viral replication (36,38,39,71). It has been demonstrated that DDX3 binds the HCV core FIGURE 8.…”
Section: Discussionmentioning
confidence: 99%
“…One prerequisite for a cellular protein to be subjected to such a modification would likely be a close interaction with RT so that it can gain access to the RT active site. The RT protein is known to interact with a number of cellular proteins, including molecular chaperone proteins (13,15), the helicase DDX3 (52), and the translation factor eIF4E (22). The RT protein is also thought to be cytotoxic when overexpressed and has been reported to affect cellular functions such as interferon signaling and gene expression (2,8,14,53).…”
Section: Discussionmentioning
confidence: 99%
“…Replication of the genome occurs by reverse transcription of the pregenomic RNA template, is mediated by the HBV polymerase which binds to an RNA stem loop and occurs entirely within nucleocapsids. It was recently shown that DDX3 binds to HBV polymerase, in an interaction that did not appear to be mediated by RNA [43]. DDX3 was incorporated into nucleocapsids together with HBV polymerase and inhibited the initial step of reverse transcription in a manner that seemed to 25 depend on the ATPase-activity of DDX3 [43].…”
Section: Ddx3 Inhibits Hbv Replicationmentioning
confidence: 99%
“…It was recently shown that DDX3 binds to HBV polymerase, in an interaction that did not appear to be mediated by RNA [43]. DDX3 was incorporated into nucleocapsids together with HBV polymerase and inhibited the initial step of reverse transcription in a manner that seemed to 25 depend on the ATPase-activity of DDX3 [43]. A lot of questions remain unanswered, such as the exact mechanism of inhibition and the physiological relevance of the finding.…”
Section: Ddx3 Inhibits Hbv Replicationmentioning
confidence: 99%
See 1 more Smart Citation